Preference test of sound among multiple alternatives in rats. - Ryo Soga; Tomoyo Isoguchi Shiramatsu; Hirokazu Takahashi (PLoS ONE)
Conditioned place preference (CPP) tests in rodents have been well established to measure preference induced by secondary reinforcing properties, but conventional assays are not sensitive enough to measure innate, weak preference, or the primary reinforcing property of a conditioned stimulus. We designed a novel CPP assay with better sensitivity and efficiency in quantifying and ranking preference of particular sounds among multiple alternatives. Each test tone was presented according to the location of free-moving rats in the arena, where assignment of location to each tone changed in every 20-s session. We demonstrated that our assay was able to rank tone preference among 4 alternatives within 12.5 min (125 s (habituation) + 25 s/sessions × 25 sessions). In order to measure and rank sound preference, we attempted to use sojourn times with each test sound ([Formula: see text]), and a preference index (PI) based on transition matrices of initial and end sounds in every session. Both [Formula: see text] and PI revealed similar trends of innate preference in which rats preferred test conditions in the following order: silence, 40-, 20-, then 10-kHz tones. Further, rats exhibited a change in preference after an classical conditioning of the 20-kHz tone with a rewarding microstimulation of the dopaminergic system. We also demonstrated that PI was a more robust and sensitive indicator than [Formula: see text] when the locomotion activity level of rats became low due to habituation to the assay repeated over sessions. Thus, our assay offers a novel method of evaluating auditory preference that is superior to conventional CPP assays, offering promising prospects in the field of sensory neuroscience.